Carbon nanotube film, conductive prepreg and preparation method thereof

By spraying carbon nanotube dispersion, it forms a carbon nanotube film and is compounded with the adhesive film or prepreg, the problems of high preparation cost and poor resistance controllability of carbon nanotube film are solved, and low-cost and high-efficiency carbon nanometers are achieved Patterned resistance distribution of tubular membrane preparation and conductive prepreg.

CN119431847AActive Publication Date: 2025-02-14BEIJING GAOYI CHUANGHE AVIATION TECH CO LTD

Patent Information

Application Number
CN202411459603.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-14
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing carbon nanotube films are cost-effective, have low production efficiency, are difficult to store and transport, and cannot be cut and spliced, resulting in poor resistance controllability of conductive prepregs and cannot achieve patterned resistance distribution.

Method used

The carbon nanotubes are dispersed into water to form a uniform and stable dispersion liquid, and sprayed onto the surface of the release paper by spraying technology, and then dried to form a carbon nanotube film. The carbon nanotube film is then roll-compressed with the adhesive film or prepreg through a composite machine to form a conductive adhesive film or conductive prepreg, and the required conductive prepreg is obtained by cutting and curing.

Benefits of technology

Reduces the cost of carbon nanotube film, improves the preparation efficiency, optimizes storage and transportation methods, makes carbon nanotube film easy to cut and splice, thereby improving the resistance controllability of conductive prepregs, and achieving patterned resistance distribution .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431847A_ABST
    Figure CN119431847A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon nanotube film, a conductive prepreg and a preparation method thereof. Comprising the following steps: step 1, preparing a carbon nanotube film; 2, rolling and compounding: carrying out rolling and compounding on the carbon nanotube film and a required adhesive film through a compounding machine to form a conductive adhesive film, and compounding the conductive adhesive film and fibers to form a conductive prepreg; or carrying out rolling compounding on the carbon nanotube film and the required prepreg through a compounding machine to form a conductive prepreg; step 3, cutting and curing to obtain a conductive prepreg with a required specification; according to the carbon nanotube film, the conductive prepreg and the preparation method of the conductive prepreg, the cost of the carbon nanotube film can be effectively reduced, the preparation efficiency of the carbon nanotube film is improved, the storage and transportation modes of the carbon nanotube film are optimized, the carbon nanotube film can be conveniently cut and spliced, the resistance controllability of the conductive prepreg is improved, and the service life of the conductive prepreg is prolonged. And the patterned resistance distribution arrangement can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and particularly relates to a carbon nanotube film, a conductive prepreg and a preparation method thereof. Background Art

[0002] Carbon nanomaterials represented by carbon nanotubes have low density, high conductivity and strength and have received widespread attention and application, especially in the field of conductive materials. Carbon nanotubes have been used in antistatic, conductive adhesives, electromagnetic shielding, electromagnetic wave absorbers, sensors and many other fields.

[0003] Carbon nanotube film is one of the structural forms of carbon nanotube applications. There are two main types of existing carbon nanotube films: (1) Carbon nanotube film represented by buckypaper, which is usually obtained by vacuum filtration of carbon nanotubes dispersed in water or solvent through a microporous membrane, and its thickness ranges from tens to more than 100 microns; (2) Carbon nanotube film grown and pulled by CVD method, which has higher conductivity, its thickness ranges from several microns to tens of microns, and its surface resistance is generally below 5Ω, and has higher strength.

[0004] The above-mentioned carbon nanotube membrane represented by buckypaper is difficult to prepare a large area of ​​carbon nanotube membrane, and it also produces a large amount of wastewater or waste liquid, which is expensive. Since its preparation, it has generally been used for a small amount of scientific research. The above-mentioned method of growing carbon nanotube membrane by CVD method has been applied in batch production, but its cost is still high, with a market price of 1,000 yuan / m 2 (300 yuan / gram) or more, and its resistance control range is small, and the design space is small.

[0005] Even if the carbon nanotube coating and drying method is used to form a film, the safe and environmentally friendly water-dispersed carbon nanotube system has a high surface energy and a low viscosity, which makes it difficult to adhere to low-polarity surfaces with weak adhesion and easy peeling. It can only be coated on a surface with a higher polarity and directly integrated as a finished product, and cannot be sold, transported, and used alone in the form of a carbon nanotube film. If its viscosity is increased to a state that can be coated, a large amount of thickener is often required. The carbon nanotube film formed in this way has poor conductivity and no longer has permeability, and it needs to be washed to remove excess non-carbon nanotube substances.

[0006] Conductive adhesive film and conductive prepreg are two important applications of conductive materials. Existing conductive adhesive films usually mix conductive fillers directly into resin and then scrape the film. However, directly mixing conductive fillers into resin brings about a large number of interfaces. The conductivity of this type of carbon nanotube modified conductive adhesive film is low, usually less than 0.1S / cm, and the resistance is poorly adjustable and controllable. The conductive prepreg obtained from this has the same problem. And this method cannot obtain patterned and variable resistance distribution.

[0007] Conductive adhesive films can also be prepared by combining carbon nanotube films and adhesive films. For example, buckypaper and CVD carbon nanotube films can be laid on the surface of prepregs, but their interfaces are poor and the resistance is poorly adjustable and controllable, so it is impossible to obtain a patterned resistance distribution structure. Therefore, it is of great significance to study how to improve the resistance controllability of conductive prepregs prepared using carbon nanotube films and realize patterned resistance distribution on conductive prepregs.

[0008] The existing patent application CN202311701744.1 discloses a continuous nanoporous membrane filtration production method, which is applicable to porous membranes, but the cost of microporous membranes is very high, and the entire device process is complicated. The method of growing carbon nanotube membranes by CVD has very high equipment requirements, and the cost is still high. The resistance stability control range is generally between 1-7Ω / sq., and the design space is small. The method of preparing carbon nanotube membranes by coating, such as CN201910967180.3, applies a carbon nanotube dispersion to the surface of a roller, and then dries to obtain a carbon nanotube membrane and transfers it to the surface of other substrates. This method is only applicable to substrates infiltrated with carbon nanotube dispersions, and cannot be used for easily strippable substrates with very low surface energy. Summary of the invention

[0009] The purpose of the present invention is to provide a carbon nanotube film, a conductive prepreg and a preparation method thereof, which solves the problems existing in the prior art that the carbon nanotube film preparation cost is high, the production efficiency is low, it is difficult to store and transport, and it cannot be cut and spliced, so that the resistance controllability of the conductive prepreg prepared by using the carbon nanotube film is poor and patterned resistance distribution cannot be achieved. The cost of the carbon nanotube film can be effectively reduced, the preparation efficiency of the carbon nanotube film can be improved, the storage and transportation method of the carbon nanotube film can be optimized, the carbon nanotube film can be easily cut and spliced, and the resistance controllability of the conductive prepreg can be improved, so that it can achieve patterned resistance distribution setting.

[0010] The objectives of the present invention are achieved through the following technical solutions.

[0011] A carbon nanotube film, a conductive prepreg and a preparation method thereof, the method comprising the following steps:

[0012] Step 1, preparation of carbon nanotube film: dispersing carbon nanotubes in water to form a uniform and stable dispersion; spraying the dispersion onto the surface of release paper, and after drying, forming a carbon nanotube film adhering to the surface of the release paper;

[0013] Step 2, rolling compounding: rolling compounding the carbon nanotube film and the desired adhesive film through a compounding machine to form a conductive adhesive film, and then compounding the conductive adhesive film with fibers to form a conductive prepreg; or rolling compounding the carbon nanotube film and the desired prepreg through a compounding machine to form a conductive prepreg;

[0014] Step 3: cutting and curing to obtain the conductive prepreg of required specifications.

[0015] Furthermore, in step 1, the thickness of the carbon nanotube film is 0.5 μm-80 μm.

[0016] Furthermore, the surface resistance of the carbon nanotube film is 10-10000Ω.

[0017] Furthermore, in step 2, at least one layer of carbon nanotube film is provided.

[0018] Further, step one includes:

[0019] Step S11: dispersing the carbon nanotubes into water under the action of a dispersant to form a uniform and stable dispersion;

[0020] Step S12: by controlling the aperture of the nozzle to be the first aperture d1, the dispersion is first sprayed onto the release paper and then dried to form a continuous carbon nanotube microfilm;

[0021] Step S13: by controlling the aperture of the nozzle to be the second aperture d2, the dispersion is first sprayed onto the release paper and then dried to form a continuous carbon nanotube film adhered to the surface of the release paper.

[0022] Furthermore, the concentration of carbon nanotubes in the dispersion is 0.5 wt%-3.5 wt%.

[0023] Furthermore, the spraying and drying processes are performed at least once.

[0024] Furthermore, d1<d2.

[0025] Furthermore, the dispersion also includes a polymer binder, and the total mass of the dispersant and the polymer binder is no more than twice that of the carbon nanotubes.

[0026] A carbon nanotube film, the preparation method of which is included in the preparation method of a conductive prepreg containing the carbon nanotube film, the carbon nanotube film comprises carbon nanotubes and a dispersant; the amount of the dispersant is 5%-40% of the mass of the carbon nanotubes; the carbon nanotube film is compounded with an adhesive film to obtain a conductive adhesive film.

[0027] A conductive prepreg is prepared by the method for preparing a conductive prepreg containing a carbon nanotube film, and the conductive prepreg contains a conductive adhesive film.

[0028] The beneficial effects of the present invention are as follows: through the carbon nanotube film, conductive prepreg and preparation method thereof, the cost of the carbon nanotube film can be effectively reduced, the preparation efficiency of the carbon nanotube film can be improved, the storage and transportation methods of the carbon nanotube film can be optimized, the carbon nanotube film can be easily cut and spliced, and the resistance controllability of the conductive prepreg can be improved, so that it can realize patterned resistance distribution setting. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings, which constitute part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention. In the accompanying drawings:

[0030] Figure 1 It is a schematic diagram of the process flow chart of carbon nanotube film preparation;

[0031] Figure 2 Schematic diagram of preparing conductive adhesive film or conductive prepreg by rolling of a composite machine;

[0032] Figure 3 Schematic diagram of the conductive prepreg structure with patterned resistor distribution.

[0033] Reference numerals: 1, carbon nanotube film; 2, release paper; 3, upper roller; 4, lower roller. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0035] A carbon nanotube film, a conductive prepreg and a preparation method thereof. The preparation method of the conductive prepreg containing the carbon nanotube film comprises the following steps:

[0036] Step 1, preparation of carbon nanotube film 1: dispersing carbon nanotubes in water to form a uniform and stable dispersion; spraying the dispersion onto the surface of release paper 2, and after drying, forming a carbon nanotube film 1 adhering to the surface of release paper 2;

[0037] Step 2, rolling compounding: rolling compounding the carbon nanotube film 1 and the desired adhesive film through a compounding machine to form a conductive adhesive film, and then compounding the conductive adhesive film with fibers to form a conductive prepreg; or rolling compounding the carbon nanotube film 1 and the desired prepreg through a compounding machine to form a conductive prepreg;

[0038] Step 3: cutting and curing to obtain the conductive prepreg of required specifications.

[0039] Through the method, the cost of the carbon nanotube film 1 can be effectively reduced, the preparation efficiency of the carbon nanotube film 1 can be improved, the storage and transportation methods of the carbon nanotube film 1 can be optimized, the carbon nanotube film 1 can be easily cut and spliced, and the resistance controllability of the conductive prepreg can be improved, so that it can achieve patterned resistance distribution setting.

[0040] Wherein, in step 1, the carbon nanotube film 1 is formed by stacking carbon nanotubes and dispersants, the carbon nanotube film 1 is adhered to the release paper 2, the thickness of the carbon nanotube film is 0.5μm-80μm, the surface resistance of the carbon nanotube film 1 is 10-10000Ω, and the mass of the dispersant in the carbon nanotube film 1 is 5%-40% of the carbon nanotube. In step 2, the carbon nanotube film 1 is provided with at least one layer. During the rolling process of the composite machine, the upper roller 3 of the composite machine can adopt a hot pressing roller with a pattern, and the lower roller 4 is a round roller; the specific types of the upper roller 3 and the lower roller 4 are set as required. The distribution of the carbon nanotube film 1 on the conductive adhesive film presents the required pattern. Specifically, the carbon nanofilm can be cut into the required pattern, and under the action of the hot pressing roller with the corresponding pattern, it is rolled with the adhesive film to form a conductive adhesive film with the required pattern. Wherein, the carbon nanotube film 1 with at least one resistor is distributed on the conductive adhesive film.

[0041] Step one includes:

[0042] Step S11: dispersing the carbon nanotubes into water under the action of a dispersant to form a uniform and stable dispersion; wherein the amount of the dispersant is 5%-40% of the mass of the carbon nanotubes; and the concentration of the carbon nanotubes in the dispersion is 0.5wt%-3.5wt%.

[0043] Step S12: by controlling the aperture of the nozzle to be the first aperture d1, the dispersion is first sprayed onto the release paper 2 and then dried to form a continuous carbon nanotube microfilm; the number of spraying and drying treatments is set at least once;

[0044] Step S13: by controlling the aperture of the nozzle to be the second aperture d2, the dispersion is first sprayed onto the release paper 2 and then dried to form a continuous carbon nanotube film 1 adhering to the surface of the release paper 2;

[0045] Wherein, d1<d2, the specific values ​​of d1 and d2 are set as required. The number of times the dispersion is sprayed is recorded as n, and the initial preset number of sprays is m, and n and m are both positive integers; m<n. Preferably; when n is greater than 4, in the process of spraying the dispersion n times, before the carbon nanotubes cover the release paper, the median size of the droplet of the spray sprayed with the initial preset number of sprays m times is between 3μm-60μm, and m is 1-4. Wherein, when the median diameter is controlled to be higher than 3μm, the droplets are not completely dried before reaching the surface of the release paper 2, and can be well adsorbed on the surface of the release paper 2; when the diameter is controlled to be lower than 60μm, the thickness of the microfilm formed by the carbon nanotubes before covering most of the surface of the release paper 2 is small, and the effect on the final film thickness is small, and the small diameter droplets have a high density of microfilms formed after being sprayed on the surface of the release paper 2 due to their small diameter, which is more conducive to the uniform spreading of the droplets on the surface of the release paper during subsequent spraying; so the uniformity of the carbon nanotube film 1 obtained in the end is high. The types of dispersants include any one or more of sodium dodecylbenzene sulfonate, sodium stearate, polyvinyl pyrrolidone, and Triton X-100.

[0046] Different from the background technology, the existing methods include carbon nanotube membranes represented by buckypaper, which are generally obtained by nanoporous membrane filtration method. However, it is obviously difficult to prepare large-area carbon nanotube membranes, and the price of nanoporous membranes is very high. The filtration method has high energy consumption and cannot be produced continuously, resulting in its high price. Generally, only the area is ≤0.1m 2 The present invention uses a method of multiple spraying to first form a micro-droplet film on the surface of the release paper 2, so that the surface of the non-wetting release paper 2 becomes a wetted surface, and then spraying can form a continuous carbon nanotube film 1. Thus, a carbon nanotube film 1 is successfully prepared on the release paper 2 with low surface polarity (see Example 1 for details). In principle, a method of multiple spraying is used. Under the initial preset number of spraying times m, the micro-droplets formed by spraying are first dried on the release paper 2 to form a carbon nanotube micro-film with high surface polarity. When the micro-film covers the preset surface area of ​​the release paper 2, the surface of the release paper 2 becomes hydrophilic, and subsequent micro-droplets of different diameters can be well spread and dried on the surface of the release paper 2, and finally a continuous and uniform carbon nanotube film 1 is formed. Among them, the preset surface area is the area occupying most of the surface of the release paper 2, which is specifically set according to the requirements. Compared with the existing methods, the present application has the following advantages:

[0047] (1) Low cost: The present application uses a carbon nanotube aqueous dispersion spraying method to prepare a carbon nanotube film 1 attached to a release paper 2. Currently, carbon nanotube production has been scaled up, and the price of carbon nanotubes has dropped to less than 0.2 yuan / g. This preparation method can continuously prepare a roll of carbon nanotube film 1. When multiple nozzles are used, the preparation efficiency is as high as 1000-4000 m 2 / h, the equipment requirements are simple, thus significantly reducing costs. Its cost is as low as 1-20 yuan / m 2 , which is much lower than the 1000 yuan / m2 of CVD carbon nanotube film 1 2 .

[0048] (2) High productivity: This preparation method can continuously prepare rolled carbon nanotube films1 with a production efficiency of up to 1000-4000 m 2 / h, the equipment can use conventional spraying equipment.

[0049] (3) Easy to store and transport: The carbon nanotubes attached to the release paper 2 can be stored and transported in rolls at a low cost.

[0050] (4) Ease of use: The carbon nanotube film 1 can be used at any time. At least one carbon nanotube film 1 with different resistance can be combined with a film or prepreg to prepare a multi-resistance film or prepreg. Because it is distributed on the release paper 2, it can be cut into various shapes at will. Then, it is laid on the film or prepreg to form a film and prepreg with various conductive patterns on the surface. It can also cooperate with the raised pattern on the hot pressing roller to emboss the carbon nanotubes with the same pattern on the film and prepreg to form a patterned film and prepreg. This is something that existing carbon nanofilms such as buckypaper and carbon nanotube film 1 cannot do.

[0051] (5) Good material properties such as composite material process matching. This carbon nanotube film 1 matches the requirements of the composite material molding process and meets the requirements of resin permeability. The resulting composite material has good interlaminar shear strength. After adding a small amount of soluble thermoplastic resin, the interlaminar shear strength of the composite material can be further improved. Especially after adding thermoplastic particles, the carbon nanotube film 1 has good permeability, good resin penetration, few interlaminar defects of the composite material, and high interlaminar shear strength.

[0052] In addition, in order to match the molding process of the adhesive film and the composite material, the carbon nanotube film 1 needs to have good permeability, and a high amount of dispersant seriously affects the permeability of the resin in the carbon nanotube film 1, thereby deteriorating the interlayer performance of the composite material after the carbon nanotube film 1 is distributed between the composite material layers. As shown in Table 1, under the premise of acceptable dispersibility, the performance of the composite material is given priority. Therefore, the preferred amount of dispersant is 5-40% of the amount of carbon nanotubes.

[0053] Table 1 Effect of dispersant dosage on interlaminar shear strength of T800 / 5228 composite materials

[0054]

[0055] Preferably, the dispersion can also include a polymer binder; used to improve the interlaminar shear strength of the composite material, and the amount of the binder is set as required. As shown in Table 2, considering the balance between permeability and strength, preferably, the total mass of the dispersant and the polymer binder does not exceed 2 times that of the carbon nanotubes. The polymer binder is a thermosetting resin or thermoplastic resin with a glass transition temperature higher than 150°C.

[0056] Table 2 Effect of soluble polymer binder dosage on interlaminar shear strength of T800 / 5228 composite materials

[0057]

[0058] The dispersion also includes a granular toughening agent; the amount of the toughening agent is set as required. Preferably, the total amount of the toughening agent does not exceed 10 times the mass of the carbon nanotubes. This is to prevent the problem of excessive toughening agent dosage leading to a decrease in the conductivity of the carbon nanotube film 1. Preferably, the granular toughening agent is a thermoplastic resin particle; it is used to significantly increase the resin permeability of the carbon nanotube film 1 while improving the interlaminar shear strength of the composite material, as shown in Table 3.

[0059] Table 3 Effect of the amount of insoluble thermoplastic resin particles on the interlaminar shear strength of T800 / 5228 composite materials

[0060]

[0061] In addition, the carbon nanotube film 1 also includes a sheet-like conductive nanomaterial; the sheet-like conductive nanomaterial includes any one or more of graphene and nanographite sheets; it can slightly improve the conductivity of the carbon nanotube film 1. The amount of the sheet-like conductive nanomaterial does not exceed 20% of the carbon nanotube content in the carbon nanotube film; in order to prevent the problem of significantly reduced interlayer performance of the prepared carbon nanotube film 1 due to decreased resin permeability and poor graphene-resin interface. The details are shown in Table 4.

[0062] Table 4 Effect of graphene dosage on interlaminar shear strength of T800 / 5228 composite materials

[0063]

[0064] A carbon nanotube film, the preparation method of which is included in the preparation method of a conductive prepreg containing the carbon nanotube film, the carbon nanotube film comprises carbon nanotubes and a dispersant; the carbon nanotube film is compounded with an adhesive film to obtain a conductive adhesive film.

[0065] A conductive prepreg is prepared by the method for preparing a conductive prepreg containing a carbon nanotube film, and the conductive prepreg contains a conductive adhesive film.

[0066] Embodiment 1:

[0067] The implementation process of the technical solution of this embodiment is as follows:

[0068] (1-1) 150 g of carbon nanotubes (with a diameter of 8-10 nm and a tube length of 25 μm) were added to 9900 g of deionized water, and 15 g of sodium dodecylbenzene sulfonate was added as a dispersant. The mixture was ultrasonically dispersed for 0.5 h, and dispersed 5 times in total. After the dispersion was completed, the undispersed carbon nanotubes were removed by centrifugation to obtain a carbon nanotube aqueous dispersion with a concentration of 1.2%;

[0069] (1-2) The spraying machine uses 5 rows of nozzles, injects the dispersion as the spraying liquid into the liquid storage tank, adjusts the nozzle and air pressure, controls the median diameter of the droplets sprayed by the first two rows of nozzles to be between 10 μm, and the median diameter of the droplets sprayed by the last three rows of nozzles to be 50 μm, 50 μm, and 80 μm, respectively. After the release paper 2 is inserted into the unwinding-winding device of the reciprocating spraying machine, the machine is turned on, and the release paper 2 moves forward at a speed of 0.5 m / s. The hot air drying device between the nozzles is controlled at 150°C. The carbon nanotube film 1 attached to the surface of the release paper 2 is wound up, with a thickness of 7.1 μm and a surface resistance of 280Ω, named C280 carbon nanotube film 1;

[0070] (1-3) The epoxy resin 5228A film and the carbon nanotube film 1 are compounded by roller pressing in a compounding machine to obtain a conductive epoxy resin 5228A film JM5228A-C280;

[0071] (1-4) The epoxy resin carbon fiber prepreg T800 / 5228A and the carbon nanotube film 1 are rolled and compounded by a compounding machine, and a single-sided compound is used to obtain a conductive epoxy resin carbon fiber prepreg T800 / 5228A-C280;

[0072] (1-5) Compounding the conductive epoxy resin film JM5228A-280 obtained in (1-3) above with continuous carbon fiber to form a conductive epoxy resin carbon fiber prepreg T800 / 5228A-C280-2;

[0073] (1-6) The conductive epoxy resin carbon fiber prepreg T800 / 5228A-C280 obtained above is cut into a size of 300mmх300mm, including 8 sheets at 0° and 8 sheets at 45°, and is laid in a quasi-isotropic manner. After being cured using the epoxy resin curing process, a conductive modified composite material is obtained.

[0074] The conductive modified composite material has a high thickness conductivity of 0.27S / cm and a 0° interlaminar shear strength of 93MPa.

[0075] Embodiment 2:

[0076] The implementation process of the technical solution of this embodiment is as follows:

[0077] (2-1) adding 220 g of carbon nanotubes (with a diameter of 3-5 nm and a tube length of 15 μm) to 9900 g of deionized water, adding 25 g of graphene, and then adding 75 g of sodium stearate as a dispersant, and dispersing by high-speed shearing for 6 h. After the dispersion, the undispersed carbon nanotubes were removed by centrifugation to obtain an aqueous dispersion having a carbon nanotube concentration of 1.9% and a graphene concentration of 0.15% (total conductive agent concentration of 2.05%);

[0078] (2-2) The spraying machine uses 3 rows of nozzles, injects the dispersion as the spraying liquid into the liquid storage tank, adjusts the nozzle and air pressure, inserts the release paper 2 into the unwinding-winding device of the reciprocating spraying machine, turns on the machine, and adopts the reciprocating spraying mode. The median diameters of the droplets sprayed by the three nozzles in the first 3 times are controlled to be 5μm, 20μm, and 40μm respectively. After 2 reciprocating times, the surface of the release paper 2 is completely covered with black. Then the median diameter of the droplets sprayed by the nozzle is adjusted to 70μm, and then reciprocated 3 more times. During spraying, the temperature of the hot air drying device between the nozzles is controlled at 150°C. After the reciprocating is completed, the release paper 2 with the carbon nanotube film 1 is rolled forward and replaced with a blank release paper 2 to continue spraying. The carbon nanotube film 1 attached to the surface of the release paper 2 is rolled up, with a thickness of 27μm and a surface resistance of 78Ω, named CG78 carbon nanotube film 1;

[0079] (2-3) The epoxy resin film BA9916 and the carbon nanotube film 1 are compounded by roller pressing in a compounding machine to obtain a conductive epoxy resin film JM9916-C78;

[0080] (2-4) The T700 / BA9916 epoxy resin carbon fiber prepreg and the carbon nanotube film 1 are rolled and compounded by a compounding machine, and a single-sided compound is used to obtain a conductive epoxy resin carbon fiber prepreg T700 / BA9916-C78;

[0081] (2-5) Compounding the conductive epoxy resin film JM9916-C78 obtained in (2-3) above with continuous carbon fiber to form a conductive epoxy resin carbon fiber prepreg T700 / BA9916-C78-2;

[0082] (2-6) The conductive epoxy resin carbon fiber prepreg T700 / BA9916-C78 obtained above is cut into a size of 300mmх300mm, including 8 sheets at 0° and 8 sheets at 45°, and laid in a quasi-isotropic manner. After curing using the epoxy resin curing process, a conductive modified composite material is obtained.

[0083] The conductive modified composite material has a high thickness conductivity of 0.48S / cm and a 0° interlaminar shear strength of 82MPa.

[0084] Embodiment 3:

[0085] The implementation process of the technical solution of this embodiment is as follows:

[0086] (3-1) 250 g of carbon nanotubes (with a diameter of 8-10 nm and a tube length of 25 μm) were added to 10 kg of deionized water, and 60 g of sodium dodecylbenzene sulfonate was added as a dispersant. The mixture was dispersed by ultrasonication for 0.5 h, and dispersed 5 times in total. The mixture was then ball-milled for 1 h. After the dispersion was completed, the undispersed carbon nanotubes were removed by centrifugation to obtain a carbon nanotube aqueous dispersion with a concentration of 2.2%;

[0087] (3-2) The spraying machine uses 5 rows of nozzles, injects the dispersion as the spraying liquid into the liquid storage tank, adjusts the nozzle and air pressure, controls the median diameter of the droplets sprayed by the first three rows of nozzles to be 10 μm, 20 μm and 40 μm respectively, and the median diameter of the droplets sprayed by the last two rows of nozzles to be 70 μm and 100 μm respectively, inserts the release paper 2 into the unwinding-winding device of the reciprocating spraying machine, turns on the machine, and the release paper 2 moves forward at a speed of 0.8 m / s. The hot air drying device between the nozzles is controlled at 150°C. The carbon nanotube film 1 attached to the surface of the release paper 2 is wound up, with a thickness of 15 μm and a surface resistance of 210Ω, named C210 carbon nanotube film 1;

[0088] (3-3) The bismaleimide resin film QY9611 and the carbon nanotube film 1 are compounded by roller pressing in a compounding machine to obtain a conductive epoxy resin film JM9611-C210;

[0089] (3-4) CCF800 / QY9611 bismaleimide resin carbon fiber prepreg and carbon nanotube film 1 are rolled and compounded by a compounding machine, and single-sided compounding is adopted to obtain conductive bismaleimide resin carbon fiber prepreg CCF800 / QY9611-C210;

[0090] (3-5) Compounding the conductive bismaleimide resin film JM210 obtained in (3-3) above with continuous carbon fiber to form a conductive bismaleimide resin carbon fiber prepreg CCF800 / QY9611-C210-2;

[0091] (3-6) The conductive bismaleimide resin carbon fiber prepreg YJ210 obtained above is cut into a size of 300mmх300mm, including 8 sheets at 0° and 8 sheets at 45°, and laid in a quasi-isotropic manner. After curing using the bismaleimide resin curing process, a conductive modified composite material CCF800 / QY9611-C210 is obtained.

[0092] (3-7) Water-soluble carboxyl modified PEK-C was added to the carbon nanotube aqueous dispersion in (3-1) in an amount of 100 g, and then used for spraying. The other steps were the same as (3-2)-(3-6). The obtained carbon nanotube film 1 had a resistance of 810Ω (CT810) and a film thickness of 21 μm, and a conductive modified composite material CCF800 / QY9611-CT810 was obtained.

[0093] (3-8) In the carbon nanotube aqueous dispersion in (3-1), non-water-soluble PEK-C micron particles with a particle size of 10-20 μm and an addition amount of 340 g are added, and then used for spraying. The other steps are the same as (3-2)-(3-6). The obtained carbon nanotube film 1 has a resistance of 770Ω (CT770) and a film thickness of 39 μm, and a conductive modified composite material CCF800 / QY9611-CT770 is obtained.

[0094] CCF800 / QY9611-C210 has a high thickness conductivity of 0.35S / cm, and a 0° interlaminar shear strength of 76MPa. CCF800 / QY9611-CT810 has a thickness conductivity of 0.29S / cm, and a 0° interlaminar shear strength of 95MPa. CCF800 / QY9611-CT770 has a thickness conductivity of 0.34S / cm, and a 0° interlaminar shear strength of 98MPa.

[0095] Embodiment 4:

[0096] The implementation process of the technical solution of this embodiment is as follows:

[0097] (4-1) 93 g of carbon nanotubes (with a diameter of 7-10 nm and a tube length of 50 μm) were added to 9900 g of deionized water, and 12 g of polyvinyl pyrrolidone was added as a dispersant. The mixture was dispersed by sand milling for 2 h. After the dispersion was completed, the undispersed carbon nanotubes were removed by centrifugation to obtain a carbon nanotube aqueous dispersion with a concentration of 0.87%;

[0098] (4-2) The spraying machine uses 3 rows of nozzles, injects the dispersion as the spraying liquid into the liquid storage tank, adjusts the nozzle and air pressure, controls the median diameter of the droplets sprayed by the first 2 rows of nozzles to be 5 μm and 15 μm respectively, and the median diameter of the droplets sprayed by the last row of nozzles to be 80 μm, inserts the release paper 2 into the unwinding-winding device of the reciprocating spraying machine, turns on the machine, and the release paper 2 moves forward at a speed of 0.8 m / s. The hot air drying device between the nozzles is controlled at 150°C. The carbon nanotube film 1 attached to the surface of the release paper 2 is wound up, with a thickness of 1.8 μm and a surface resistance of 3600Ω (C3600);

[0099] (4-3) The BA9916 epoxy resin film and the carbon nanotube film 1 are rolled and laminated by a laminating machine to obtain a single resistor conductive epoxy resin film JM9916-C3600;

[0100] (4-4) The carbon nanotube films 1CG78, C280, CT810, and C3600 obtained in the above-mentioned Examples 1-4 are cut into short rolls with a width of 100 mm, and then compounded with a 400 mm wide bismaleimide film in the order of increasing resistance from left to right to obtain four types of bismaleimide films JM70-280-810-3600 with continuous distribution of resistance and conductivity, and the films are inserted into the middle layer of the composite material product, wherein the composite material is a composite material obtained by orthogonally laying 8 layers of QW280 / QY9611 prepreg, and when laying the prepreg, the film JM70-280-810-3600 is placed in the middle layer, and then the composite material product is cured according to the curing process of QW280 / QY9611. The composite material has good surface wave absorption function.

[0101] Embodiment 5:

[0102] The implementation process of the technical solution of this embodiment is as follows:

[0103] (5-1) 180 g of carbon nanotubes (with a diameter of 3-5 nm and a tube length of 35 μm) were added to 9900 g of deionized water, and 15 g of Triton X-100 was added as a dispersant. The mixture was ground using a ball mill for 3 h. After grinding, the undispersed carbon nanotubes were removed by centrifugation to obtain a carbon nanotube aqueous dispersion with a concentration of 1.55%;

[0104] (5-2) The spraying machine uses 5 rows of nozzles, injects the dispersion as the spraying liquid into the liquid storage tank, adjusts the nozzle and air pressure, controls the median diameter of the droplets sprayed by the first two rows of nozzles to be 10μm and 20μm, and the median diameter of the droplets sprayed by the last three rows of nozzles to be 40μm, 60μm and 100μm, inserts the release paper 2 into the unwinding-winding device of the reciprocating spraying machine, turns on the machine, and the release paper 2 moves forward at a speed of 0.2m / s. The hot air drying device between the nozzles is controlled at 150°C. The carbon nanotube film 1 attached to the surface of the release paper 2 is wound up, with a thickness of 12.5μm and a surface resistance of 135Ω (C135);

[0105] (5-3) The epoxy resin 5228A film and the carbon nanotube film 1 are laminated by roller pressing of a laminating machine, wherein a cross pattern is arranged on the surface of one roller, the length and height of a single cross are 80 mm respectively, the end lengths of the cross are 10 mm, and the horizontal and vertical spacings of the cross are 50 mm respectively, to obtain a conductive epoxy resin film JM5228-135TA with a conductive pattern of a cross carbon nanotube film 1 having a resistance of 135 Ω printed on the surface;

[0106] (5-4) The quartz fiber, the conductive epoxy resin film JM5228-135TA, and the conventional epoxy resin film are compounded by roller pressing in a compounding machine to obtain a conductive epoxy resin quartz fiber prepreg QW280 / 5228A-135TA with a patterned carbon nanotube film 1 on one side;

[0107] (5-5) The patterned conductive epoxy resin quartz fiber prepreg QW280 / 5228A-135TA obtained above is cut into a size of 600mmх600mm, of which 16 sheets are 0°, and orthogonally laid in layers. After curing using the epoxy resin curing process, a conductive patterned modified quartz fiber reinforced epoxy resin-based composite material is obtained.

[0108] The 0° interlaminar shear strength of the conductive modified composite material reaches 93 MPa, and it has good low-frequency wave absorbing performance.

[0109] Table 5 Technical parameters and material properties in each embodiment

[0110]

[0111] As shown in Table 5, through Examples 1-5, it can be seen that: the conductive prepreg prepared by the preparation method of the present invention has the characteristics of a large controllable range of film thickness and a large adjustable range of resistance. In addition, a carbon nanotube film 1 with a toughening function can be prepared, and the carbon nanotube film 1 is particularly suitable for the preparation of conductive adhesive films, prepregs and composite materials.

[0112] Comparative Example 1:

[0113] The implementation process of this comparative technical solution is as follows:

[0114] (DB1) 180 g of carbon nanotubes (with a diameter of 3-5 nm and a tube length of 35 μm) were added to 9900 g of deionized water, and 15 g of Triton X-100 was added as a dispersant. The mixture was ground using a ball mill for 3 h. After grinding, the undispersed carbon nanotubes were removed by centrifugation to obtain a carbon nanotube aqueous dispersion with a concentration of 1.55%;

[0115] (2) After the release paper 2 is inserted into the unwinding-winding device of the wet-process dipping machine, the carbon nanotube aqueous dispersion is poured into the dipping machine, and the release paper with a carbon nanotube film on the surface is prepared by the dip coating method. The release paper 2 moves forward at a speed of 0.2 m / s. At the same time, a hot air drying device is added between the liquid outlet of the release paper 2 and the winding device, and the temperature of the hot air drying device is controlled at 150°C.

[0116] In this comparative example, since the carbon nanotube aqueous dispersion does not infiltrate the surface of the release paper, after the release paper 2 is pulled out of the liquid surface, the liquid is almost completely debonded, and a small amount of liquid beads remain on the paper surface, and the release paper with a carbon nanotube film on the surface cannot be prepared.

[0117] By comparing Examples 1-5 with Comparative Example 1, it can be seen that the preparation method in the present application can be used for substrates with very low surface energy that are easy to peel off, such as release paper 2; and can make the process of preparing the carbon nanotube film 1 simpler and reduce the cost of preparing the carbon nanotube film 1.

[0118] In addition, through the setting of the above-mentioned preparation method, the required large-area high-permeability carbon nanotube film can be prepared simply, quickly and at low cost, and this carbon nanotube film has the characteristics of a large controllable resistance range, high accuracy and small discreteness. Through the preparation method, the film thickness range can be large and the production efficiency is high on the basis of small equipment investment; in addition, the prepared carbon nanotube film 1 is easy to roll, store, transport and reuse in various occasions; it can also be used to prepare various conductive films and prepregs, and has good process matching with the film and composite material, good interlayer performance of the composite material, and the pattern of resistance distribution is controllable, which has high process applicability. In addition, the prepared carbon nanotube film 1 can be cut and spliced, which is helpful for preparing conductive films and prepregs with various resistance distributions; the modification space is large and can match various applications. Through the preparation method, it is conducive to directly using it in the preparation of conductive films or prepregs, and it is conducive to expanding the controllable range of conductivity. It can also realize the pattern distribution of carbon nanotube film 1 on conductive prepregs, so as to prepare conductive films and prepregs with conductive patterning.

[0119] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a conductive prepreg containing a carbon nanotube film, characterized in that: The method comprises the following steps: Step 1, preparation of carbon nanotube film: dispersing carbon nanotubes in water to form a uniform and stable dispersion; spraying the dispersion onto the surface of release paper, and after drying, forming a carbon nanotube film adhering to the surface of the release paper; Step 2, rolling compounding: rolling compounding the carbon nanotube film and the desired adhesive film through a compounding machine to form a conductive adhesive film, and then compounding the conductive adhesive film with fibers to form a conductive prepreg; or rolling compounding the carbon nanotube film and the desired prepreg through a compounding machine to form a conductive prepreg; Step 3: cutting and curing to obtain the conductive prepreg of required specifications.

2. The method for preparing a conductive prepreg containing a carbon nanotube film according to claim 1, characterized in that: In the step 1, the thickness of the carbon nanotube film is 0.5 μm-80 μm.

3. The method for preparing a conductive prepreg containing a carbon nanotube film according to claim 2, characterized in that: The surface resistance of the carbon nanotube film is 10-10000Ω.

4. The method for preparing a conductive prepreg containing a carbon nanotube film according to claim 1, characterized in that: In the step 2, at least one layer of carbon nanotube film is provided.

5. The method for preparing a conductive prepreg containing a carbon nanotube film according to claim 1, characterized in that: The step one comprises: Step S11: dispersing the carbon nanotubes into water under the action of a dispersant to form a uniform and stable dispersion; Step S12: by controlling the aperture of the nozzle to be the first aperture d1, the dispersion is first sprayed onto the release paper and then dried to form a continuous carbon nanotube microfilm; Step S13: by controlling the aperture of the nozzle to be the second aperture d2, the dispersion is first sprayed onto the release paper and then dried to form a continuous carbon nanotube film adhered to the surface of the release paper.

6. The method for preparing a conductive prepreg containing a carbon nanotube film according to claim 5, characterized in that: The concentration of carbon nanotubes in the dispersion is 0.5 wt % to 3.5 wt %.

7. The method for preparing a conductive prepreg containing a carbon nanotube film according to claim 5, characterized in that: The spraying and drying processes are performed at least once.

8. The method for preparing a conductive prepreg containing a carbon nanotube film according to claim 5, characterized in that: The d1<d2.

9. The method for preparing a conductive prepreg containing a carbon nanotube film according to claim 5, characterized in that: The dispersion also includes a polymer binder, and the total mass of the dispersant and the polymer binder is no more than twice that of the carbon nanotubes.

10. A carbon nanotube film, characterized in that: The preparation method of the carbon nanotube film is included in the preparation method of a conductive prepreg containing a carbon nanotube film as described in claims 1-9, the components of the carbon nanotube film include carbon nanotubes and a dispersant; the amount of the dispersant used is 5%-40% of the mass of the carbon nanotubes; the types of the dispersant include any one or more of sodium dodecylbenzene sulfonate, sodium stearate, polyvinyl pyrrolidone, TritonX-100; the polymer binder is a thermosetting resin or thermoplastic resin with a glass transition temperature higher than 150°C; the carbon nanotube film is compounded with the adhesive film to obtain a conductive adhesive film.

11. A conductive prepreg, characterized in that: The conductive prepreg is prepared by the method for preparing a conductive prepreg containing a carbon nanotube film according to claims 1 to 9, and the conductive prepreg comprises a conductive adhesive film.

Citation Information

Patent Citations

  • Preparation method of water-soluble carbon nanotube electrothermal film

    CN110740530A

  • Carbon nanotube film and continuous preparation device system and preparation method thereof

    CN117682509A

  • Weak impregnated prepreg of carbon-containing nanotube and preparation method thereof

    CN109942854A

  • Interface assembly large-area uniform carbon material film as well as preparation method and application thereof

    CN110240155A

  • Carbon nanotube material and preparation method thereof

    CN116496537A

Cited By

  • Self-sensing and self-heating basalt fiber composite material and preparation method thereof

    CN119898084A

  • Wire duct for rail transit vehicle and preparation process and construction process thereof

    CN121332371A